1985
DOI: 10.1136/thx.40.9.668
|View full text |Cite
|
Sign up to set email alerts
|

Does bronchography have a role in the assessment of patients with haemoptysis?

Abstract: The results of bronchography in 96 consecutive patients investigated for haemoptysis at Papworth Hospital from 1975 to 1983 were reviewed. None of the patients included in this study gave a history suggestive of bronchiectasis and neither chest radiography nor fibreoptic bronchoscopy had shown a cause for the bleeding. Bronchography was performed through the fibreoptic bronchoscope and all included in the study showed both lungs adequately. The chest radiographic appearances were compared with the bronchograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Adelman et al8 found one carcinoma during follow-up of 67 patients with an initially normal bronchoscopy, and Jones et al 9 reported two peripheral carcinomas becoming evident during follow-up of 96 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adelman et al8 found one carcinoma during follow-up of 67 patients with an initially normal bronchoscopy, and Jones et al 9 reported two peripheral carcinomas becoming evident during follow-up of 96 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ist die Bronchoskopie nicht diagnostisch, das native Röntgenbild negativ und die Gerinnung unauffällig sollten ein Angio-CT und eine Echokardiographie angeschlossen werden.Bezüglich der Diagnostik von Lungenembolien (Infarkten) hat dieses Vorgehen inzwischen einen höhe-ren Stellenwert als die Perfusionsszintigraphie [11].Die früher häufig angeschlossene Bronchographie [12] gilt heute als nicht mehr zeitgemäß, sie ist durch die Computertomographie abgelöst worden. Bei Bronchiektasen liefert diese auch genügend Informationen, um einen operativen Eingriff planen zu können.…”
Section: Weiterführende Diagnostikunclassified